The Effectiveness of Transtheoretical Model to Reduce Compulsive Internet Use of Senior High School Students - Indah, Yevin Fitri Kuspar; Ramli, M; Lasan, Blasius Boli (Jurnal Kajian Bimbingan dan Konseling, 2018)
This research aims at examining the effectiveness of transtheoretical model to reduce compulsive internet use of Senior High School students. This research employed single subject design approach. The subject of this research is four students of X graders at St. Joseph Senior High School Malang which obtained high compulsive internet use score. This research utilized transtheoretical model counseling guidebook, compulsive internet use scale, observation and interview guidebook. The results of significant visual and score margin between pre-test and post-test indicate that transtheoretical model is effective to reduce compulsive internet use among Senior High School students.